Uji Aktivitas Alelopati dan Fitotoksisitas Ekstrak Daun Tabat Barito (Ficus Deltoidea Jack.) terhadap Perkecambahan dan Pertumbuhan Gulma Pletekan (Ruellia Tuberosa L.) - Dwi Susanto; Hetty Manurung; Ratna Kusuma; Samsurianto (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Tabat Barito (Ficus deltoidea Jack.) plant has secondary metabolite compounds and several bioactivities. This study was conducted to test the allelopathic activity and phytotoxicity of methanol extract of Tabat Barito leaves against Pletekan weed (Ruellia tuberosa L.) The study used a completely randomized design (CRD) in two experimental stages, namely the seed germination stage and the plant growth stage, using the concentration of methanol extract of Tabat Barito leaves: 0%, 25%, 50%, and 75%. The results showed that the methanol extract of F. deltoidea leaves was able to inhibit the germination process of R. tuberosa weed seeds. The highest allelopathic power and phytotoxicity were produced at a concentration of 75%, which is significantly different from the other treatments. At the growth stage, the methanol extract of F. deltoidea reduced biomass (wet weight 76%; dry weight 67%), chlorophyll a 50%, chlorophyll b 50%, and total chlorophyll by 71%. The higher the F. deltoidea leaf methanol extract concentration, the higher the allelopathic power and phytotoxicity against weed growth. The study showed that the methanol extract of F. deltoidea leaves was able to inhibit weed germination and growth and had strong phytotoxicity power against Pletekan weed, so F. deltoidea leaf extract has the potential to be used as a source of allelopathy or natural herbicide ingredients (bio-herbicides) that are environmentally friendly substitutes for chemical herbicides against weed plants.